ABSTRACTS OF THE PROCEEDINGS OF THE XXXIXth ANNUAL SCIENTIFIC CONFERENCE OF THE PHYSIOLOGICAL SOCIETY OF NIGERIA : 26-30 October, 2021, Bayero University, Kano, Kano State, Nigeria (Nigerian Journal of Physiological Sciences, 2022)
ABSTRACTS OF THE PROCEEDINGS OF THE XXXIXth ANNUAL SCIENTIFIC CONFERENCE OF THE PHYSIOLOGICAL SOCIETY OF NIGERIA26-30 October, 2021, Bayero University, Kano, Kano State, Nigeria